Sacred versus Pseudo-Sacred Values: How People Cope with Taboo Trade-Offs - Tetlock, Philip E.; Mellers, Barbara A.; Scoblic, J. Peter (American Economic Review, 2017)
Psychologists have documented widespread public deference to “sacred values” that communities, formally or informally, exempt from tradeoffs with secular limits, like money. This work has, however, been largely confined to low-stakes settings. As the stakes rise, deference must decline because people can't write blank checks for every “sacred” cause. Shadow pricing is inevitable which sets the stage for political blame-games of varying sophistication. In a rational world, citizens would accept the necessity of such tradeoffs, but the attraction to moral absolutes is strong–perhaps even essential for social cohesion.